IMMUNOHISTOCHEMISTRY STUDIES IN A CASE OF DERMATITIS HERPETIFORMIS DEMONSTRATE COMPLEX PATTERNS OF REACTIVITY - Ana Maria Abreu Velez; Jorge Oliver; Michael S. Howard (Our Dermatology Online, 2013)
Introduction: Dermatitis herpetiformis (DH) is an autoimmune, clinically pleomorphic, papulovesicular disorder sometimes associated with celiac disease and gluten sensitivity. DH is categorized by subepidermal vesicles and bullae on hematoxylin and eosin (H&E) staining, and with immunoglobulin A deposits present along the dermal papillary tips on direct immunofluorescence (DIF). Case Report: We describe a 50 year old female that presented with sudden onset pruritus and clinical blisters, predominantly on extensor areas of the extremities. Biopsies for H&E examination, as well as immunohistochemistry (IHC) and DIF analysis were performed. Results: H&E examination demonstrated subepidermal blistering; within the blister lumen, numerous neutrophils were present, with occasional eosinophils and lymphocytes also seen. DIF examination revealed linear deposits of IgA along the epidermal basement membrane zone, associated with other immunoglobulins and complement. IHC examination showed similar patterns of reactivity to IgA, and also to other immunoreactants. Cells positive for CD1a were present within the blisters, correlating with S-100 staining. Cells staining positive for CD8, CD45 and occasionally CD4 and Granzyme B were seen not only in the blister lumens, but also around neurovascular packages under the blisters. Finally, CD2 positive cells were found around the upper dermal blood vessels. Discussion: Focal DIF linear IgA deposition is the classic hallmark diagnostic finding in DH. However, it is possible that genetic susceptibility and environmental triggers also play a crucial role in the pathogenesis, often acting via cellular pathways exhibiting disease-associated polymorphisms. In tolerance breakthrough, the initiating antigen presenting cells likely lead to immune system cell differentiation, and activation of adaptive immunity.